ETNOGRAFI: MEMBUAT DATA BERCERITA - Ninuk Kleden-Probonegoro (LIPI Press, 2012)
This article aims to show how one can organize ethnographic data in such a way that these data can â€œtell a storyâ€. As a social and human science method ethnography has been used by almost all researchers of socio-cultural problems in a manner in which it is treated as something given as if anything could go in it and it can be interpreted according to oneâ€™s own will. As a result, ethnography is deprived of its own meaning, and loses its nature as a means of story-telling while lacking its ability to account for the story it produces. This is the reason which has motivated my effort to objectify in this article what an ethnography should be like and how as a social science method it can describe a socio-cultural reality or an imagination, and even can make an imagination the very reality which a thick description can bring about. Qualitative ethnographic data can tell a story at diagnostic or interpretive level. In so doing ethnographic descriptions become accountable because these are based on an epistemological ground.